One-pot catalyst-switching synthesis of thermoresponsive amphiphilic diblock copolymers consisting of poly(N, N-diethylacrylamide) and biodegradable polyesters. Issue 15 (22nd March 2023) - Fu, Xiangming; Wang, Yanqiu; Xu, Liang; Narumi, Atsushi; Sato, Shin-ichiro; Shen, Xiande; Kakuchi, Toyoji
Abstract : A method for the syntheses of thermoresponsive amphiphilic diblock copolymers through sequential organocatalyzed polymerizations using group transfer polymerization (GTP) and ring-opening polymerization (ROP), respectively, is described. Abstract : A method for the syntheses of thermoresponsive amphiphilic diblock copolymers through sequential organocatalyzed polymerizations of vinyl-based and lactone-based monomers using group transfer polymerization (GTP) and ring-opening polymerization (ROP), respectively, is described. The organocatalysts were switched between the two polymerization stages and all syntheses could be conducted in a one-pot manner. The polymerization systems directly produced diblock copolymers composed of poly( N, N -diethylacrylamide) and biodegradable polyesters (poly(ε-caprolactone), poly(trimethylene carbonate), and poly(l -lactide) in various content ratios. Aqueous solutions of the obtained block copolymers below their cloud point temperatures ( T cp ) were carefully characterized, revealing a close relationship among the structures of the block copolymers, T cp, and micellar forming properties below the T cp .